Introduction and Importance of the Science of Hadith and Mention of Renowned Muhaddithin: علم حدیث کا تعارف اور اہمیت اور معروف محدثین کا تذکرہ - Shakeel, Ms. Alina; Kakar, Dr. Farida; Tahir, Mufti Abdul (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
The word Hadith in the Arabic language is used for various meanings and contexts. In Arabic, Hadith means conversation, a new matter, or an important and notable event. Anything new, significant, or worthy of mention, a conversation, or a discourse, is referred to as Hadith in Arabic. The plural of Hadith is Ahadith, derived from the singular word Ahdoothah, meaning a particular or prominent thing remembered by people. However, among the Muhaddithin (scholars of Hadith), the plural Ahadith has been commonly used since the beginning. From a linguistic perspective, Ahadith is the plural of Ahdoothah. It signifies any news or matter, whether related to religion or worldly affairs. In the terminological sense, scholars of Hadith, linguists, and experts in principles have provided slightly varying definitions. Hadith can also mean a conversation, an event, or a story. In Islamic terminology, Hadith refers to the sayings, actions, and approvals of the Prophet Muhammad (ﷺ). When the term Ilm al-Hadith (the science of Hadith) is used in technical terms, it refers to all matters and subjects aimed at verifying the sayings, actions, and states of the Prophet Muhammad (ﷺ). The word Hadith is derived from Tahdith, which means "to inform." Hence, any saying, action, or approval attributed to the Prophet (ﷺ) is referred to as Hadith. Before the advent of Islam, Arabs used the term Hadith in the sense of "informing" or "news." For instance, they referred to their famous events as Ahadith. The root of the word Hadith always carries the meaning of conveying information, regardless of how it is transformed. Some scholars also associate the word Hadith with the concept of novelty, making it the opposite of Qadeem (ancient). In this sense, they consider Qadeem as the Book of Allah and Jadeed (new) as the sayings of the Prophet Muhammad (ﷺ). According to the sayings of the Prophet (ﷺ), only two things hold ultimate significance: Kalam (speech) and Tariqah (path). Thus, the best speech is the speech of Allah, and the best path is the one followed by Muhammad (ﷺ). Most books of Hadith include the phrase Inna Ahsan al-Hadith Kitab Allah ("Indeed, the best Hadith is the Book of Allah"). In contrast, Ibn Majah uniquely uses the term Ahsan al-Kalam ("the best speech"). This distinction suggests that some scholars, out of caution and piety, avoided referring to the divine scripture, which is eternal, as Hadith. However, it is clear that the science of Hadith serves as a critical means to preserve and authenticate the sayings, actions, and approvals of the Prophet Muhammad (ﷺ), which are second only to the Qur'an in importance for Muslims.